Los videos tutoriales para el fortalecimiento del razonamiento matemático en la escuela rural (2021)
This article is based on a research work whose objective was to strengthen the competence of mathematical reasoning from spatial thinking and geometric systems in fifth grade students in an   educational center in a rural sector through didactic sequences supported by tutorial videos that helped improve performances for meaningful learning.  The approach of the project was qualitative with an action research design. As techniques were used participating observation, diagnostic tests, development of didactic sequences as evidence of student production, field diary and final test. Both diagnostic and final tests allowed to evaluate the level of performance of fifth students in the area of mathematics, specifically in spatial thinking and geometric systems, it was of great interest to know Ausubel's theory to strengthen meaningful learning and the structure proposed by Tobón for the construction of didactic sequences which helped improve performances in the area.